Epidemic situation and features of accompanying therapy in the treatment of socially significant infectious diseases in penitentiary populations before, during, and after the COVID-19 pandemic - V. M. Kolomiets; N. A. Polshikova; A. Yu. Petrov; A. L. Kovalenko; E. V. Talikova (Антибиотики и Химиотерапия)
The aim of the study was to identify the dynamics on the incidence of major socially significant infectious diseases (SIDs) before, during, and after the COVID-19 pandemic in penitentiary populations. The effectiveness of accompanying therapy was assessed using the example of clinical observation of comorbid widespread destructive pulmonary tuberculosis.Material and methods. Statistical reporting data on the administrative unit of the Federal Penitentiary Service of one of the constituent entities of the Russian Federation was analyzed. Verification of diagnosis and treatment was carried out using generally accepted methods in accordance with regulatory documentation and standards of therapy. At the first stage, the dynamics of incidence for the periods 2000–2019 (before the COVID-19 pandemic) and 2020–2022 (against the background and after the COVID-19 pandemic) was analyzed . The second stage of the study was the analysis of data on tuberculosis (TB): features of the clinical course, etiotropic treatment, and the possibility of increasing efficiency through accompanying therapy.Results. At the first stage of epidemiological data analysis, it was revealed that in the pre-pandemic period, the incidence of SIDs in the Federal Penitentiary Facilities decreased. HIV infection was the exception, the incidence of which increased by 3.8 times during this period. The COVID-19 pandemic did not have a significant impact on the formation of the epidemiological situation. However a change in the structure of the pathology was noted: multidirectional dynamics were recorded in parasitic infections — a 1.8-fold increase (from 38.7 to 69.5 per 100 thousand people) in scabies and a 2.8-fold decrease (from 290.4 to 104.2 per 100 thousand) in head lice (P>0.05). Moreover, all cases were detected in pre-trial detention centers when detainees were admitted to them; these diseases were not recorded in correctional facilities. The same pattern of incidence was noted for the main sexually transmitted infections: against the background of a 4.5-fold increase in trichomoniasis (from 58.1 to 260.6 per 100 thousand) a 4.4-fold decrease in the incidence of syphilis (from 154.9 to 34 .7 per 100 thousand), (P>0.05) was recorded. At the same time, the incidence of TB and HIV infection has almost halved. A further decrease in the incidence of the main SIDs was recorded in the post-Covid period (2020–2022). The exceptions were gonorrhea (a 1.8-fold increase — from 18.2 to 32.7 per 100 thousand) and tuberculosis (a 1.5-fold increase — from 364.8 to 552.1 per 100 thousand), P>0.05. At the second stage, it was noted that TB/HIV comorbidity in combination with viral hepatitis remains a problem in correctional facilities. In this regard, accompaniment therapy becomes an important element of treatment — in the event of the adverse events development in response to the main (etiotropic) therapy, in particular. The presented clinical case describes the positive effect of including remaxol, a polyionic infusion hepatotropic drug, in the treatment regimen for comorbid common destructive TB/HIV and poor tolerability of anti-tuberculosis drugs, which helped reduce the severity of hepatotoxicity and made it possible not to introduce changes to the main treatment regimen.